The utopia of the beaches of Saturn. (socio-psychology, epistemology and excitement of utopias) (Polis (Santiago), 2018)
The paper considers the socio-psychological and epistemological utopia, and utopia arises connected with emotion. Check the conditions of economic modernization and democratization that have led to the disbelief of utopias, and the values that give identity to individuals who adopt them. It emphasizes the need to reformulate the conception of the phenomenon of power and its practices, and the importance that the educational task is to re-enchant new generations utopias.
Keywords: utopia; economic modernization; democratization